Pengaruh Kepemimpinan, Disiplin dan Motivasi Terhadap Kinerja Guru Di Smk Se-Kecamatan Wonomulyo Kabupaten Polewali Mandar - Muchlis; Abd Rahman; Nurdin Latif (STIM-LPI Makassar, 2023)
The purpose of this study was to determine the influence of leadership, discipline and motivation both partially and simultaneously on teacher performance. The research method is ex post facto with a population of 121 teachers for the research sample using proportional random sampling so that a sample of 55 respondents is obtained. Data collection techniques using documentation and questionnaires. The data analysis technique uses the t test and F test. The results of this study can be concluded that there is an influence of leadership, discipline and motivation both partially and simultaneously on teacher performance in SMK Se Wonomulyo District, Polewali Mandar Regency.